National trade facilitation bodies in the world (United Nations GenevaCH, 2014)
Presents an in-depth analysis of 50 trade facilitation bodies. Provides quantitative analysis of existing national trade faciliation bodies an first-hand set of recommendations extracted from the experiences of participating stakeholders.
Keywords: TRADE FACILITATION